Confederacy of Ambition : William Winlock Miller and the Making of Washington Territory - Lang, William L. (Book collections on Project MUSE., 2014)
The promise of opportunity drew twenty-seven-year-old Illinois schoolteacher William Winlock Miller west to the future Washington Territory in 1850. Like so many other Oregon Trail emigrants Miller arrived cash-poor and ambitious, but unlike most he fulfilled his grandest ambitions. By the time of his death in 1876, Miller had amassed one of the largest private fortunes in the territory and had used it creatively in developing the region's assets, leaving a significant mark on the territory's political and economic history.